Design and evaluation of a dehumidifying plaster panel for passive architecture integration. - Melero-Tur, Sofía; García-Morales, Soledad; Neila-González, Francisco Javier (Revista de la Construcción. Journal of Construction, 2015)
Buildings Indoor Air Quality requires a control in the Relative Humidity parameter. In passive architecture in humid climates relative humidity is even more important for human comfort and difficult to control. Therefore, nowadays, there is a research on dehumidifying systems. The present article shows an innovative dehumidifying panel composed of a plaster and Calcium Chloride salt. Laboratory tests are carried out to establish its viability as an indoor air moister regulator integrated in common plaster building interior coatings. There are two types of tests that have been carried out in two consecutive empirical phases: in the first phase, the tests of characterization of the Calcium Chloride as a desiccant are carried out; in a second phase, the dehumidifying panel as a whole is tested. Finally, both types of empirical tests show the efficiency and viability as an air moisture passive control system.